The Capacity of Volunteers in The Reproductive Health Education Program For Adolescents in East Jakarta - Retnowati, Elais; Lestari, Retno Dwi; Sutisna, Anan (JIV-Jurnal Ilmiah Visi, 2024)
The training management procedures for PMI volunteers have not been implemented continuously due to the limited resources of this non-profit organization. This study aims to explore the capacity of volunteers after one year of training and task placement in the Reproductive and Sexual Health Program for adolescents. A qualitative approach was used to analyze the volunteers' knowledge and skills, with data collected through interviews and questionnaires involving 26 respondents. The results indicate that the volunteers' overall capacity is adequate to fulfill their roles, supported by commitment, solidarity, and the ability to share experiences. However, competency in handling cases of sexual violence remains inconsistent among volunteers. Volunteers with less than five years of experience tend to provide brief responses when assisting victims of sexual violence. The study recommends implementing regular, continuous training schedules and establishing forums or communities for volunteer experience-sharing. The outcomes of these discussions can serve as the basis for developing case-based guidebooks and FAQ lists. These learning resources are expected to enhance the capacity of new volunteers, ensuring the program's sustainability.